Pragmatics across languages and cultures - Trosborg, Anna, 1937- (Handbooks of pragmatics ;, 2010)
This handbook provides a comprehensive overview, as well as breaking new ground, in a versatile and fast growing field. It contains 4 sections: Contrastive, Cross-cultural and Intercultural Pragmatics, Interlanguage Pragmatics, Teaching and Testing of Second/Foreign Language Pragmatics, and Pragmatics in Corporate Culture Communication, covering a wide range of topics, from speech acts and politeness issues to Lingua Franca and Corporate Crises Communication. The approach is theoretical, methodological as well as applied, with a focus on authentic, interactional data. All articles are written by renowned leading specialists, who provide in-depth, up-to-date overviews, and view new directions and visions for future research.